Sustainable mitigation of heavy metals from effluents: Toxicity and fate with recent technological advancements. Issue 1 (1st January 2021) - Gaur, Vivek Kumar; Sharma, Poonam; Gaur, Prachi; Varjani, Sunita; Ngo, Huu Hao; Guo, Wenshan; Chaturvedi, Preeti; Singhania, Reeta Rani
ABSTRACT: Increase in anthropogenic activities due to rapid industrialization had caused an elevation in heavy metal contamination of aquatic and terrestrial ecosystems. These pollutants have detrimental effects on human and environmental health. The majority of these pollutants are carcinogenic, neurotoxic, and are very poisonous even at very low concentrations. Contamination caused by heavy metals has become a global concern for which the traditional treatment approaches lack in providing a cost-effective and eco-friendly solution. Therefore, the use of microorganisms and plants to reduce the free available heavy metal present in the environment has become the most acceptable method by researchers. Also, in microbial- and phyto-remediation the redox reaction shifts the valence which makes these metals less toxic. In addition to this, the use of biochar as a remediation tool has provided a sustainable solution that needs further investigations toward its implementation on a larger scale. Enzymes secreted by microbes and whole microbial cell are considered an eco-efficient biocatalyst for mitigation of heavy metals from contaminated sites. To the best of our knowledge there is very less literature available covering remediation of heavy metals aspect along with the sensors used for detection of heavy metals. Systematic management should be implemented to overcome the technical and practical limitations in the use of these bioremediation techniques. The knowledge gaps have been identified in terms of its limitation and possible future directions have been discussed.